Biotechnological Propagation of Medicinal Plants and Evaluation of their Pharmacological Quality - Ozoda, Sunnatova; Feruza, Mustafayeva; Oftoboy, Qo‘ziyeva; Xolida, Sanakulova (American Journal of Biology and Natural Sciences, 2025)
The purpose of this research is to determine the pharmacological activity of medicinal plants and to study the effectiveness of their propagation processes. The research focuses on the pharmacological characteristics of three medicinal plants — Aloe Vera, Basil (Rayhon), and Lavender — and evaluates their antibacterial and antifungal effects under laboratory conditions. The plants showed high antibacterial and antifungal activity, while the propagation and cultivation processes were found to be easy and efficient. The results of this study indicate the potential of these plants to be used as natural therapeutic agents, providing opportunities for their application in the production of medicinal products.